Beyond Economic Growth: Reassessing Economic Development as a Driver of Sustainable Development Goal Achievement - Prof. Dr. Afaq Ali Khan; Shumaila Khan; Abdul Jabar; Dr. Samrana Afzal (Inverge Journal of Social Sciences, 2026)
The purpose of this study is to reassess the role of economic development as a driver of Sustainable Development Goal (SDG) achievement by comparing GDP-centric metrics with multidimensional frameworks that incorporate human development, institutional quality, and environmental sustainability. Using a balanced panel dataset of 139 countries over the period 2010–2024, this study estimates hierarchical fixed effects models to quantify the explanatory power of traditional versus expanded development indicators. Three progressive models were estimated: a GDP-centric baseline, a human development expanded model, and a fully specified "Beyond GDP" multidimensional model. System GMM estimation and alternative dependent variables were employed as robustness checks. Results show that while GDP per capita is a significant predictor in baseline models (β = 4.82, p < 0.001), its effect diminishes substantially and becomes statistically insignificant (β = 0.92, p = 0.18) once human development (HDI), governance (WGI_Avg), and renewable energy share are controlled for. The fully specified multidimensional model explains 83% of the variation in SDG Index scores—a 25-percentage-point improvement over the GDP-only baseline (Adjusted R² = 0.58). Robustness checks using System GMM and alternative dependent variables confirm these findings. The study relies on internationally standardized datasets with some indicators inconsistently reported in low-income countries. The panel design controls for time-invariant country effects but cannot fully capture context-specific dynamics. The 2010–2024 window excludes earlier decades limiting insights into long-term structural transformations. The findings provide empirical validation for the UN's "Beyond GDP" initiative and offer actionable insights for policymakers seeking to accelerate 2030 Agenda implementation. Governments should adopt multidimensional dashboards for national planning, prioritize institutional quality and anti-corruption reforms, and accelerate green energy transitions with pro-poor design. This study provides robust empirical evidence that economic growth alone is neither necessary nor sufficient for SDG achievement; rather, multidimensional capabilities, particularly human capital, institutional integrity, and green transitions, are the true drivers of sustainable progress. The hierarchical modelling approach demonstrates that multidimensional frameworks do not merely "add noise" but fundamentally improve explanatory power and policy relevance. References Aevoae, G. M., Dicu, R. M., Mardiros, D. N., & Scorțescu, F. I. (2026). Towards sustainable development: New insights into the factors affecting human development in EU countries. Sustainability, 18(15), 7686. https://doi.org/10.3390/su18157686 Akdağ, İ. (2026). Sustainable development indicators and economic growth: Evidence from seven strategic emerging economies (2002–2023). Sustainability, 18(3), 1529. https://doi.org/10.3390/su18031529 Alkire, S., Evans, M., & Foster, J. (2025). Beyond GDP: What multidimensional measures of poverty and well-being add to dashboards and composite indices (United Nations Committee for Development Policy Background Paper No. 60). United Nations Department of Economic and Social Affairs. Al Kium, A., Sarker, S., Shikha, S. A., Kamal, M. A. T., Jabed, M. I. K., Munifa, N. K., ... & John, D. B. (2023). Health equity and digital disparities in cancer screening and cardiovascular care across socioeconomic and ethnic groups: A systematic review. Vascular and Endovascular Review, 6(2), 35–44. Arum, H. S., Tasriani, & Miftah, D. (2026). Determinants of the Human Development Index in Indonesia in the perspective of Maqasid al-Shariah. Ar-Ribh: Jurnal Ekonomi Islam. Article page Attridge, S., & Gouett, M. (2021). Development finance institutions: The need for bold action to invest better. ODI. Berglof, E., Muralidharan, K., & Pangestu, M. (2024). External review of the Worldwide Governance Indicators. Chen, L., Shuai, C., Chen, X., & Zhao, B. (2025). A data-driven framework for assessing global progress towards sustainable development goals. Sustainable Production and Consumption, 60, 217–228. https://doi.org/10.1016/j.spc.2025.10.001 Chin, V., Osman, D., & Allan, B. (2026, February 19). Beyond GDP: A shared opportunity for growth and job creation. Boston Consulting Group. Boston Consulting Group article COVACIU, L.-N. (2026). Sustainable development convergence in Central and Eastern Europe: A panel analysis based on the SDG Index. Review of Management and Economic Engineering, 25(2), 68–80. https://doi.org/10.71235/rmee.258 D’Adamo, I., Della Sciucca, M., Gastaldi, M., & Lupi, B. (2025). Indicator assessment of sustainable development goals: A global perspective. Sustainability, 17(18), 8259. https://doi.org/10.3390/su17188259 Deswal, S., & Deswal, P. (2025). The Sustainable Development Goals (SDGs): A comprehensive review of progress, implementation, and the path forward. International Journal of Technology, Health and Sustainability, 1(2), 133–141. Ekinci, G. (2025). The impact of maternal and child health on sustainable development goals: Evidence from Turkic Republics (2000–2020). BMC Public Health, 25, 4031. https://doi.org/10.1186/s12889-025-25172-z Hamid, A., & AlObaid, R. O. H. (2025). Achieving sustainable development goals: Do governance and foreign direct investment matter? Humanities and Social Sciences Communications, 12, 1727. https://doi.org/10.1057/s41599-025-05992-5 Hoekstra, R., Jansen, A., Wang, R., & Behrens, P. (2026, April 22). We need to end the GDP-obsession and put human and planetary wellbeing at the heart of policy. Frontiers Planet Prize. https://doi.org/10.25453/fpprize.32065935 Iqbal, U. (2024). AI-enhanced network optimization for electric vehicle charging infrastructure expansion in the United States using graph theory and demand analytics. Journal of Engineering and Computational Intelligence Review, 2(2), 112–129. Iqbal, U. (2025a). AI-driven predictive maintenance for US smart manufacturing: Deep learning models for equipment failure prediction and operational resilience. Journal of Engineering and Computational Intelligence Review, 3(1), 114–138. Iqbal, U. (2025b). AI-powered supplier risk intelligence: Predicting financial and geopolitical supply chain disruptions in US critical industries. Journal of Engineering and Computational Intelligence Review, 3(2), 173–193. Iqbal, U., & Bhutto, Y. (2026). Digital transformation through artificial intelligence and advance business analytic in American operational management. Journal of Theoretical and Applied Econometrics, 3(1), 37–50. Jabed, M. I. K., Ahmed, M. P., Tofa, F. M., Islam, M. F., Gomes, C. A., & Sirazy, R. M. (2026). Federated intrusion detection for Internet of Medical Things networks: Differential privacy, non-IID robustness, and cross-device generalization. Journal of Computer Science and Technology Studies, 8(8), 303–315. Jabed, M. I. K., Imran, M., Khan, A. A., Mehedi, M., Islam, A., & Pervez, R. (2026). Explainable machine learning framework for early heart disease detection using SMOTE and SHAP. Vascular and Endovascular Review, 9(1), 316–324. Jabed, M. I. K., Sirazy, M. R. M., Mandal, S., Akter, S. A., Hassan, A., & Esa, H. (2026). Developing AI-based financial forecasting and cybersecurity systems for the US digital economy. Frontiers in Computer Science and Artificial Intelligence, 5(5), 30–38. Jansen, A., Wang, R., Behrens, P., & Hoekstra, R. (2024). Beyond GDP: A review and conceptual framework for measuring sustainable and inclusive wellbeing. The Lancet Planetary Health, 8(9), e695–e705. https://doi.org/10.1016/S2542-5196(24)00147-5 Jones, A. (2026, July 9). Beyond GDP: Rethinking prosperity for future generations. Horizon Magazine, European Commission. European Commission article Kubiszewski, I., Costanza, R., Eastoe, J., Lu, T., Mulder, K., Hernandez, G. P., Benczúr, P., & Dixson-Declève, S. (2025). Building consensus on societal wellbeing: A semantic synthesis of indicators to move beyond GDP. Ecological Indicators, 178, 114076. https://doi.org/10.1016/j.ecolind.2025.114076 Leogrande, A., Arnone, M., Costantiello, A., & Drago, C. (2026). ESG determinants of financial development: Integrating econometrics and machine-learning evidence. Journal of Risk and Financial Management, 19(4), 279. Mansour, M., Zureigat, B. N., Alharasis, E. E., Abozeid, H. O., Alomair, A., & Saleh, M. W. (2026). Does carbon performance mediate the link between ESG performance and corporate tax avoidance? Sustainability, 18(14), 6978. Məmmədov, Z. A. H. İ. D. (2026). Benchmarking Türkiye’s sustainable development performance: SDG interactions, macroeconomic predictors, and explainable machine learning evidence from selected major Muslim economies. Obura, D., Agrawal, A., Christie, M., Fromentin, J.-M., Harrison, P. A., Jones, M., O’Brien, K., Pauchard, A., Roy, H. E., Settele, J., & Stoett, P. (2026). A systems reset for sustainable development. Communications Sustainability, 1, 3. https://doi.org/10.1038/s44458-025-00009-3 Organisation for Economic Co-operation and Development. (2026). Bridging the gaps for sustainable development: Coherent policies for water, energy, industry and cities. OECD Publishing. https://doi.org/10.1787/d6b60ea7-en Ozcan, B., Eryilmaz, S., & Zeren, F. (2026). Determinants of sustainable development goals in Sub-Saharan Africa: The roles of foreign direct investment inflows, environmental taxes, and natural resource rents. Economic Change and Restructuring, 59(2), 35. https://doi.org/10.1007/s10644-026-09976-6 Prabhakar, A. (2026). Reassessing pathways to sustainable economic development: An analytical investigation of global SDG progress. Journal of Recycling Economy & Sustainability Policy, 5(1), 69–77. Article page Rahman, M. A., Devnath, R. K., Niloy, S. B., Mehedi, C. M., Chowdhury, T. H., & Jabed, M. I. K. (2025, October). A stacking ensemble framework for predicting employee turnover: Explainable AI with SHAP. In 2025 IEEE 2nd International Conference on Computing, Applications and Systems (COMPAS) (pp. 1–6). IEEE. Rahman, M. A., Jabed, M. I. K., Devnath, R. K., Mehedi, C. M., Begum, M., & Mahmud, T. (2026). MSRFF: An interpretable CNN–Vision Transformer framework for diabetic retinopathy detection. In 2026 2nd International Conference on Computational Intelligence Approaches and Applications (ICCIAA). IEEE. https://doi.org/10.1109/ICCIAA68481.2026.11543580 Stavytskyy, A., & Dligach, A. (2025). The global economic model in crisis: An analysis of the obstacles to the sustainable development goals. Sustainability, 17(19), 8537. Tzivanakis, N., Melios, G., & Moore, H. L. (2026). Measuring what matters: A systematic review of social service coverage in Beyond-GDP indicators. UCL Institute for Global Prosperity. van den Bergh, J. (2026). ‘Beyond GDP’ requires replacement, not just additional metrics. Social Indicators Research, 182(2), 35. Velvizhi, V. (2026). Beyond GDP: Measuring welfare in a changing global economy. International Journal of Research and Scientific Innovation, 13(4), 2988–[page range not provided]. https://doi.org/10.51244/IJRSI.2026.1304000253 World Bank. (2007). World development indicators database. World Bank. World Bank. (2023). World Development Indicators database. World Bank.